2011
DOI: 10.1038/aps.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitor MG-132 induces C6 glioma cell apoptosis via oxidative stress

Abstract: Aim: Proteasome inhibitors have been found to suppress glioma cell proliferation and induce apoptosis, but the mechanisms are not fully elucidated. In this study we investigated the mechanisms underlying the apoptosis induced by the proteasome inhibitor MG-132 in glioma cells. Methods: C6 glioma cells were used. MTT assay was used to analyze cell proliferation. Proteasome activity was assayed using Succinyl-LLVY-AMC, and intracellular ROS level was evaluated with the redox-sensitive dye DCFH-DA. Apoptosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Taken together, we conclude that PL inhibits proteasome activity, which may lead to the accumulation of ROS as a secondary effect, as was demonstrated previously for other proteasome inhibitors [23,24]. Since proteasome inhibitors may elevate intracellular ROS by inducing ER stress [25] and by inhibiting FOXM1 [16], which has been shown to induce the expression of ROS scavengers [26], their essential proteasome inhibitory activity may be overlooked.…”
Section: Resultssupporting
confidence: 66%
“…Taken together, we conclude that PL inhibits proteasome activity, which may lead to the accumulation of ROS as a secondary effect, as was demonstrated previously for other proteasome inhibitors [23,24]. Since proteasome inhibitors may elevate intracellular ROS by inducing ER stress [25] and by inhibiting FOXM1 [16], which has been shown to induce the expression of ROS scavengers [26], their essential proteasome inhibitory activity may be overlooked.…”
Section: Resultssupporting
confidence: 66%
“…Early induction of oxidative stress that precedes proteasome inhibition is a specific feature of thiostrepton-induced cytotoxicity not shared by other proteasome inhibitors such as MG132 and bortezomib known to produce oxidative stress downstream of proteasomal and mitochondrial impairment [57,58]. However, the specific molecular mechanism underlying thiostrepton-induced dysregulation of cellular redox homeostasis observed by us is in cultured melanoma and myeloma cells remains to be elucidated, and numerous factors may contribute to thiostrepton-associated oxidative stress.…”
Section: Discussionmentioning
confidence: 97%
“…However, it should be mentioned that MG-132 not only inhibits proteasomal activity, but also produces reactive oxygen species (ROS). Previous studies showed that prolonged treatment (24 h) of MG-132 at dose of 1–30 µM induces apoptosis via formation of ROS in several cancer cell types [42], [43]. It was also reported that incubation with 25 µM of MG-132 for 4 h prevented misfolded CFTR degradation in CHO cells expressing GFP tagged F508del-CFTR [44].…”
Section: Discussionmentioning
confidence: 93%